A comparison study of bioaccessibility of soy protein gel induced by magnesiumchloride, glucono-δ-lactone and microbial transglutaminase. (September 2016) - Rui, Xin; Fu, Yuting; Zhang, Qiuqin; Li, Wei; Zare, Fatemeh; Chen, Xiaohong; Jiang, Mei; Dong, Mingsheng
Abstract: Food matrix may regulate the nutrients releasing profiles during human digestion. In the present study, soy protein gel was prepared by magnesium chloride (MgCl2 ), glucono-δ-lactone (GDL), and microbial transglutaminase (MTGase) as coagulant, respectively, and using an in vitro gastrointestinal simulated digestion (GIS) model, the effect of different coagulants on soy protein degradation was investigated. Our results showed that gel induced by MTGase, regardless of concentration, had significantly lower (P < 0.05) in vitro protein digestibility, in comparison with the other coagulants. Protein degradation occurred more rapidly at the initial phase of gastric digestion for the gel prepared with GDL rather than that of MgCl2, whereas both gels possessed an undigested 25 kDa band at the end of intestinal digestion. Also, smaller peptides (<10 kDa) gradually increased during the digestion and GDL gel reached the highest peptide content of 3.73 mg/ml after GIS. MTGase gel possessed the least peptide amount and free amino acid content at the end of GIS. The results demonstrated structure of soy protein network assembled by different coagulant had vital influence on the protein bioaccessibility. Highlights: Coagulant type influenced protein bioaccessibility of soy protein network. MTGase gel had lower in vitro protein digestibility than those of MgCl2 and GDL. MTGase gel was resistant to the in vitro gastric digestion. Both MgCl2 and GDL gels showed an undigested 25 kDa band at the end of digestion. GDL gel exerted the highest peptide content at the end of in vitro GIS digestion.